Nirmana Nada Bertautan: Alih Wahana Rupa menjadi Bunyi - Siswadi - (LP2M ISBI Bandung, 2013)
ABSTRACT This musical composition is a medium change of nirmana fine art into sound. Nirmana is a basic composition of fine art which organizing visual language in a form of level, color, line, dot, and tex- ture. Nirmana means something not meaningful or meaningless. This composition work, therefore, does not mean to convey a message or story, but simply to compose the musical elements including rhythm, melody, and harmony. As the expression media, the composition uses Javanese gamelan combined with saxophone, violin, and cello. The gamelan here just acts as a vehicle or medium of expression. The conventional patterns of gamelan music play covering form, scales, and pathet are not used in this composition. Key words: nirmana, medium change ABSTRAK Komposisi musik ini merupakan alih wahana dari seni rupa nirmana menjadi bunyi. Nir- mana merupakan komposisi dasar seni rupa yang mengorganisasikan bahasa rupa berupa bidang, warna, garis, titik dan tekstur. Nirmana artinya tidak berarti atau tidak bermakna. Dengan demikian karya komposisi ini tidak bermaksud menyampaikan pesan atau cerita, tetapi semata-mata menyusun unsur musik yang meliputi ritme, melodi dan harmoni. Se- bagai media ungkap, komposisi ini menggunakan gamelan Jawa yang digabung saxophone, biola dan cello. Gamelan di sini hanya perperan sebagai wahana atau media ekspresi. Atur- an bermain gamelan secara konvensional yang meliputi bentuk, tangga nada, dan pathet tidak digunakan dalam komposisi ini. Kata kunci: nirmana, alih wahana